CONTRIBUTION TO THE DESCRIPTION OF FAVRELLA LORENSIS (LISSON, 1907) AMMONOIDEA ZITTEL, 1884 DEL VALANGINIANO, LIMA, PERU - Villaseca Robertson, Andrea (2019)
The present study attempts to improve the original description of Favrella lorensis (Lisson, 1907) Carlos Lisson Beingolea as first time. The species was originally reported without information by international researchers. The present material was collected at the Morro Solar, Chorrillos, Lima. Seventy samples were selected from the Vera Alleman collections, deposited in the Natural History Museum “Vera Alleman Haeghebaert” in Ricardo Palma University. Favrella lorensis (Lisson, 1907) holotype T.19 (48703) is located in the Museum of Mineralogy and Paleontology of the Faculty of Geological Engineering of the National University of Engineering.  Our description was complemented adding the partial description of the suture and examples with trapezoidal section. In addition we have the first collection of Favrella lorensis (Lisson, 1907) in Peru.